Fundamental Issues and Problems that Hinder Effective Teamwork in a Merchant Bank - Abdul Rahman, Faridah Hanim (1998)
This research study was concerned with the understanding of issues and problems that hinder effective teamwork or team building in a merchant bank. The purpose of the study was to understand the concepts of effective teamwork, the related dimensions and the challenges involved in teamwork in the bank. During the preliminary stages, an exploration across various domains of literature such as leadership, team building and motivation was done in order to grasp a better understanding of the concept of team development and the requirements for effective teams in an organization. Qualitative methodology was employed in this study. An in-depth interview technique was used to obtain naturalistic data from the participants. The interviews of the ten participants from various race, sex, professions and background had been tape-recorded, transcribed and analyzed. From this study, it was found that the most common understanding of the concept of teamwork revolved around the idea t hat teamwork as means to improve organizational service and productivity. It was also largely understood that teamwork is an on-going process Apart from improving service and productivity, teamwork also encompasses other equally important dimensions, such as teamwork is a tool to improve self-control and participation in the workplace, teamwork enhance employee participation in the management's activities. The informants interviewed seemed to regard teamwork as a mean to empower employees to fully contribute and increase organizational productivity all the ten informants acknowledge the importance of teamwork They felt that teamwork is an important process for the employees and organization to respond to marketplace demands as they see teams as a better way of doing business. All the informants also agreed that the organization should provide a constructive climate for teamwork. The vision and mission statement of the organization must support team effort. The current status of teamwork in the bank as revealed by the informants was: the Bank's climate is not constructive to promote teamwork and there is inappropriate leadership. The informant's point of view is that to have a successful team, the members should be entrusted to make decisions pertaining to their job. Majority of the informants reported that the management behavior is not consistent with what they preached. The informants also reported that the structure of the Bank is not suitable for team effort, as it is high in structure and functional approach. Most of the jobs in the Bank is also focus and specialize and low dependence to one another. The interview also revealed that the management does not want to spare the time to do cross-functional training. Therefore each staff only focuses on their on work. All the informants too seem to be dissatisfied with the performance appraisal system. They reported that performance appraisal is only centered to individual performance. They also agreed that it is not easy for them to obtain information from the system as most of the information was treated as confidential. Since the Bank's organization structure is highly vertical, the status gap between one person to another is wide. The informants perceived that teamwork could not be effective if there is no equality. Since there is limited cross-functional training, the concept of teamwork that is to be able to perform multiple tasks cannot be achieved. Al l the informants agreed that the word teamwork is only a lip- service as in actual the teamwork effort is not appreciated by the power people in the Bank. Among the main problems that hinder effective teamwork: (1) They do not know how to do it - from the report by the informants, it is obvious that there is lack of skill and knowledge in developing teams; (2) They do not feel it is being rewarded - the informants reported that there is lack of apparent connections between the team effort and the formal rewards in the Bank; (3 ) People don't need teamwork and it takes too much time - most of the informants assumed that teamwork is taking a lot of their time; and lastly (4) they do not get the support from their superior - the informants reported that even though they would like to engage in teamwork, they felt that they did not get the support fr om their bosses. Majority of the informants agreed that, the Bank must undergo a reorganization program. They believed that with the current structure and system, it is quite impossible for effective teamwork. A framework for improving teamwork was made with specific recommendations for its practice and for further research.